Effect of Posterior Tibial Nerve Stimulation on Erectile Dysfunction Among Elderly Patients - Nilavan, T.; Kumaresan, Abathsagayam; Sharmila, R.; Prathap, Suganthira Babu; Vignesh, Srinivasan; Surya, Vishnuram (INTI International University, 2023)
Background and Aim: Erectile function is a complex system that involves a complex interplay between vascular, neuronal and psychological components. Genital problems are a tough issue to discuss since they are typically socially stigmatised and can cause patients to feel isolated. The aim of the study to improve the erectile functions among elderly individuals by transcutaneus posterior tibial nerve stimulation and thus improves the quality of life as well as their social and emotional well beings. Methods: This study was a pilot study involving 13 erectile dysfunction patients, conducted at saveetha institute of medical and technical science (SIMATS) for a period of 12 weeks. All the participants were assessed with Arizona sexual experience (ASEX) scale. The subjects were given Transcutaneous posterior tibial nerve stimulation for 30 minutes alternative days for 3 days a week. Result:All the procedures were conducted in a safe and comfortable environment. TPTNS produced visible motor response and tolerable sensory response in all the patients. At the end of the study, there is a positive change noted in erectile function. Comparing the baseline score and end score of ASEX, there was a significant reduction in the erectile dysfunction frequency upon the intervention. Conclusion: This study implies that TPTNS is rather helpful and faster way of treating patients with erectile dysfunction. The result showed a significant reduction in symptoms of erectile dysfunction and betterment in the quality of life.